Cysteine Proteases: Modes of Activation and Future Prospects as Pharmacological Targets - Verma, Sonia; Dixit, Rajnikant; Pandey, Kailash C. (Frontiers in Pharmacology, 2016)
Proteolytic enzymes are crucial for a variety of biological processes in organisms ranging from lower (virus, bacteria and parasite) to the higher organisms (mammals). Proteases cleave proteins into smaller fragments by catalyzing peptide bonds hydrolysis. Proteases are classified according to their catalytic site, and distributed into four major classes: cysteine proteases, serine proteases, aspartic proteases and metallo-proteases. This review will cover only cysteine proteases, papain family enzymes which are involved in multiple functions such as extracellular matrix turnover, antigen presentation, processing events, digestion, immune invasion, hemoglobin hydrolysis, parasite invasion, parasite egress and processing surface proteins. Therefore, they are promising drug targets for various diseases. For preventing unwanted digestion, cysteine proteases are synthesized as zymogens, and contain a pro-domain (regulatory) and a mature domain (catalytic). The prodomain acts as an endogenous inhibitor of the mature enzyme. For activation of the mature enzyme, removal of the prodomain is necessary and achieved by different modes. The pro-mature domain interaction can be categorized as protein-protein interactions (PPIs) and may be targeted in a range of diseases. Cysteine protease inhibitors are available that can block the active site but no such inhibitor available yet that can be targeted to block the pro-mature domain interactions and prevent it activation. This review specifically highlights the modes of activation (processing) of papain family enzymes, which involve auto-activation, trans-activation and also clarifies the future aspects of targeting PPIs to prevent the activation of cysteine proteases.